Future changes in regional inter-monthly precipitation patterns of the East Asian summer monsoon and associated uncertainty factors - Y.-H. Kim; S.-K. Min; S.-K. Min (Earth System Dynamics)
East Asia has been identified as a key area at risk of precipitation increases resulting from global warming. The East Asian summer monsoon has distinct regional inter-monthly precipitation patterns, and the simulation characteristics of global climate models therefore need to be evaluated closely to obtain reliable projections of future precipitation patterns and associated extreme events. Using metrics of inter-monthly variability in monsoon precipitation over East Asia, this study evaluates the performance of Coupled Model Intercomparison Project Phase 6 (CMIP6) models and analyzes future projections and uncertainty factors. Regional inter-monthly precipitation patterns were simulated reasonably well by the CMIP6 models but with weaker rainfall amplitudes. The CMIP6 models simulated more intense precipitation than their predecessor, the CMIP5 models, and captured observations better. Future projections indicate an overall precipitation increase during both the northward migration of the rain band and the peak monsoon time over East Asia and the three subregions, with stronger changes occurring in the higher emission scenarios. This precipitation increase can be mainly ascribed to a thermodynamic response due to the increased moisture availability associated with global warming. Internal climate variability and model uncertainty largely explained future precipitation uncertainties, which are associated with tropical ocean warming patterns. Dynamic terms explained a large portion of the model uncertainty linked to circulation changes, whereas thermodynamic terms were significantly related to scenario uncertainty.